Early Detection of Pre-Seizure using Electroencephalography for Wearable Embedded System. - SHAKIR, MOHAMED (2018)
The electroencephalography (EEG) monitoring and ‘control by thought’ technology is replacing the traditional switch mode technology, which is used as support in various fields of life including education, training, entertainment, human behaviors and for people with disabilities.